2008
DOI: 10.1016/j.socscimed.2008.03.036
|View full text |Cite
|
Sign up to set email alerts
|

The meaning of the survivor identity for women with breast cancer

Abstract: Abstract"Survivor" has become a ubiquitous and largely unquestioned term in culture and cancer discourse. While anecdotal evidence suggests women with breast cancer find fault with survivor images and discourse, the extent to which women identify with or reject the survivor identity has not been empirically studied. This paper examines whether women treated for breast cancer embrace survivorship. Data come from 39 in-depth interviews with women in the United States who completed treatment for breast cancer 3 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
185
3
24

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 226 publications
(221 citation statements)
references
References 29 publications
9
185
3
24
Order By: Relevance
“…In our study, many AABCS identified themselves as survivors, fully embracing the identity. However, these findings differed from those of a qualitative study of middle class, Caucasian, breast cancer survivors who were from 3 to 18 months after treatment and rejected the social identity as survivors (Kaiser, 2008).…”
Section: Survivor Identitycontrasting
confidence: 92%
“…In our study, many AABCS identified themselves as survivors, fully embracing the identity. However, these findings differed from those of a qualitative study of middle class, Caucasian, breast cancer survivors who were from 3 to 18 months after treatment and rejected the social identity as survivors (Kaiser, 2008).…”
Section: Survivor Identitycontrasting
confidence: 92%
“…250-253). Cancer survival cannot be definitively labeled as a one-size-fits-all experience or phase, but rather is a process of patients dealing with and understanding the impact of their illness on their lives and identities (Frank, 2003;Kaiser, 2008). Surviving cancer, especially for older adults, is a dynamic process drawing on one's illness experiences and life histories (Towsley, Beck, & Watkins, 2007).…”
Section: Relevance For Cancer Survivorshipmentioning
confidence: 99%
“…Second, disagreements remain about when the actual survivorship phase begins complicated by the changing nature of cancer diagnosis and treatment (Khan et al, 2012). Third, not everyone who survives cancer considers themselves survivors as the term implies (Jagielski, Hawley, Corbin, Weiss, & Griggs, 2012;Kaiser, 2008;Pieters & Heilemann, 2011). Frank (2003) ongoing-that they have not survived anything-so they are unable to identify with this term.…”
mentioning
confidence: 99%
“…In contrast, individual experiences of cancer survivorship underline alienation from this conceptualisation, e.g. through the threat of recurrence; having a less 'severe' cancer experience; or a desire to keep one's cancer experience private (Kaiser 2008). Although the term 'survivorship' can be a contested concept, we use it here to indicate an important social transformation rather than simply marking an individual change (Dyer 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These children therefore not only had chronic illness but also new corporeal markers of bodily difference that could be hidden or displayed and commented on by others, or play a semiotic role. Hence both the corporeal and embodied nature of identity has consequences both for the understanding of normalcy or difference and for a person's feelings of inner worth (Shilling 1993;Sharp 1995;Kaiser 2008). Significantly, as Gilleard and Higgs (2014) point out, it is important to be aware that the corporeal is often that which is seen as private while the embodied is seen as that which is social and out in the world.…”
mentioning
confidence: 99%